Pro android UI - Jackson, Wallace (Apress, 2014)
If you're an Android application developer, chances are you're using fixed, scrolling, swipe-able, and other cutting-edge custom UI Designs in your Android development projects. These UI Design approaches as well as other Android ViewGroup UI layout containers are the bread and butter of Pro Android User Interface (UI) design and Android User Experience (UX) design and development. Using a top down approach, Pro Android UI shows you how to design and develop the best user interface for your app, while taking into account the varying device form factors in the increasingly fragmented Android environment. Pro Android UI aims to be the ultimate reference and customization cookbook for your Android UI Design, and as such will be useful to experienced developers as well as beginners. With Android's powerful UI layout classes, you can easily create everything from the simplest of lists to fully tricked-out user interfaces. While using these UI classes for boring, standard user interfaces can be quite simple, customizing a unique UI design can often become extremely challenging.